Finance Act 2021 Notes: sections 42-85 and Schedules 9-15: plastic packaging tax - Pirlot, A (Sweet and Maxwell, 2021)
Notes provisions of the Finance Act 2021 ss. 42-85 and Schs 9-15 which implement a plastic packaging excise tax from April 2022 and outlines its main elements, its policy goals, and potential issues surrounding some of its design functions.